Middle School Science and Mathematics Teachers' Views on Science-Mathematics Integration - Kürşat Kurt; Kemal İzci; Mustafa Pehlivan (International Journal of Educational Spectrum, 2023)
This study was conducted to determine the opinions of middle school science and mathematics teachers about science-mathematics integration. A total of 38 teachers (19 science teachers, 19 math teachers) participated in this qualitative research. Data were collected using a semi-structured interview form. The data were evaluated with descriptive and content analysis in qualitative analysis. While all of the science teachers included in the study thought that integration was necessary, mathematics teachers expressed different opinions. While the teachers had different definitions of integration, it was determined that they generally exchanged ideas with the other branch teachers. It was determined that the most course needed integration for mathematics teachers was the Turkish and the mathematics for science teachers. According to teachers, the most important advantage of integration is that it increases student course success. As a result; although science and mathematics teachers have heard about the integration of science and mathematics, they do not have sufficient knowledge and application. For this reason, it is recommended that teachers of both branches should be informed about science-mathematics integration and integrate them into their lessons.